Knowledge and Attitudes Towards Cervical Cancer and the Human Papillomavirus Vaccine Among Women in Mukalla City, Yemen: A Cross-Sectional Study - Badheeb, Ahmed; Bawazir, Amen; Algofili, Omar; Sharqan, Abdulrhman; Al-Awbathani, Amir; Bamuqabel, Mashael; Bahurmuz, Noor; Bin Swaid, Weiam; Bahurmuz, Mona; Ahmed, Faisal (Asian Pacific Journal of Cancer Nursing, 2025)
Background: Cervical cancer is a major public health concern, especially in regions with limited screening and vaccination access. Human papillomavirus (HPV) vaccination is a vital preventive measure, yet its success depends on public knowledge and acceptance. This study assessed knowledge and attitudes regarding cervical cancer and the HPV vaccine among women in Mukalla City, Yemen. Methods: A cross-sectional survey was conducted from June to August 2023 among 425 women aged 18 years and older. A structured questionnaire captured sociodemographic data, knowledge of cervical cancer and HPV vaccination, and attitudes towards vaccination and screening. Descriptive statistics, chi-square tests, and multivariate logistic regression were used for analysis. Results: The largest participant group was aged 18–24 years (174/425; 41.0%), and 196/425 (46.0%) had secondary education. Overall, 216/425 (50.9%) demonstrated sufficient knowledge about cervical cancer and the HPV vaccine. Knowledge was significantly higher among women with college education or above (p = 0.050). Positive attitudes towards HPV vaccination were noted, with 294/425 (69.2%) supporting its inclusion in the national immunization program. Educational level was an independent predictor of sufficient knowledge (adjusted odds ratio, 1.60; 95% confidence interval, 1.00–2.50; p = 0.050). Conclusions: Substantial knowledge gaps exist regarding cervical cancer and HPV vaccination among women in Mukalla City. Despite generally positive attitudes, targeted education campaigns are essential, especially for women with lower education levels. Future research should explore sociocultural factors influencing awareness to guide public health interventions.